2016
DOI: 10.1186/s12879-016-1829-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of rotavirus and adenovirus in hospitalized children with diarrhea: a 5-year survey in Beijing

Abstract: BackgroundDiarrhea caused by viruses is a global problem among young children. We investigated two of the most important agents, rotavirus and adenovirus, to provide epidemiological evidence for a better understanding of their role among children with acute diarrhea.MethodsA total of 3147 hospitalized children were enrolled in the study during 2010 ~ 2014. Antigen testing for rotavirus and DNA testing for adenovirus were performed on stool specimens collected from participants.ResultsThere were 1985 cases of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
18
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 18 publications
8
18
2
6
Order By: Relevance
“…Our study showed that the largest group of patients comprise of children between 2 and 5 years of age and this finding is consistent with other study results (17,19,20). Also in line with other studies, the incidence of AGE in boys was slightly higher than in girls (21,22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that the largest group of patients comprise of children between 2 and 5 years of age and this finding is consistent with other study results (17,19,20). Also in line with other studies, the incidence of AGE in boys was slightly higher than in girls (21,22).…”
Section: Discussionsupporting
confidence: 93%
“…Nasze badanie potwierdza te obserwacje, gdyż w przedstawionej analizie dominowały dzieci poniżej 5 r.ż., a najliczniejszą grupę chorych stanowiły dzieci pomiędzy 2. a 5. r.ż. Również rozkład płci, w którym nieznacznie dominowali chłopcy, był zgodny z innymi doniesieniami (21,22).…”
Section: Dyskusjaunclassified
“…Moreover, the positive rates of AdV were 25.23% and 27.57% for latex agglutination test and RT‐qPCR, respectively. Both of the positive rates were relatively remarkable, while previous studies reported different prevalence rates . The results of the current research indicated that there was no significant difference ( P > .05) between the latex agglutination test and RT‐qPCR in the detection of RV and AdV.…”
Section: Discussioncontrasting
confidence: 46%
“…Rotavirus gastroenteritis is highly contagious, and most children are infected with RVA before 5 years of age . The prevalence of rotavirus diarrhea in children varies among countries, from 6.5‐38% . While infections are observed throughout the year, cases predominate in the winter and spring in many countries …”
Section: Introductionmentioning
confidence: 99%
“…15 The prevalence of rotavirus diarrhea in children varies among countries, from 6.5-38%. [16][17][18][19] While infections are observed throughout the year, cases predominate in the winter and spring in many countries. 17,[20][21][22][23] In Turkey, acute gastroenteritis is a serious public health problem, affecting over 352 000 children younger than 5 years old annually (http://tsim.saglik.gov.tr/tsim).…”
Section: Introductionmentioning
confidence: 99%